2012
DOI: 10.1108/02635571211254998
|View full text |Cite
|
Sign up to set email alerts
|

ERP use and value: Portuguese and Spanish SMEs

Abstract: Purpose-Consistent with the diffusion of innovation (DOI) model and resource-based view (RBV) theory, this paper develops a research model for measuring enterprise resource planning (ERP) post-adoption and its consequence on small and medium enterprise (SME) performance. Design/methodology/approach-The model links six determinants based on DOI to explain 'ERP use' and three determinants based on RBV to explain the 'ERP value', on which nine hypotheses are postulated. Testing was conducted through structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 35 publications
7
53
0
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 28 The results of this study confirmed those of previous studies [3,6,61]. Previous studies found that competitive pressure, training, best practices, compatibility, and efficiency are important antecedents of ERP use.…”
Section: Page 29 Of 35supporting
confidence: 92%
“…A c c e p t e d M a n u s c r i p t 28 The results of this study confirmed those of previous studies [3,6,61]. Previous studies found that competitive pressure, training, best practices, compatibility, and efficiency are important antecedents of ERP use.…”
Section: Page 29 Of 35supporting
confidence: 92%
“…Diverse educational environment levels reveal differences In fact, the southernmost region of Spain is characterized by small and medium-sized businesses, which account for 80% of total employment in the region (Gil-Pechuan, Expósito-Langa, & Tomas-Miquel, 2013;Ruivo, Oliveira, & Neto, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Stage 4 is part of the Green IT integration (i.e., formal adoption), and stage 5 is Green IT maturation (i.e., post-adoption) where Green IT is integrated into the firm's value chain activities. DOI has been used in several research areas including web development (Beatty et al 2001), enterprise resource planning (ERP) (Bradford and Florin 2003;Ruivo et al 2012), eprocurement (Li, Y.-h 2008), and radio frequency identification (Wang et al 2010). …”
Section: Diffusion Of Innovation (Doi) Theorymentioning
confidence: 99%